2015
DOI: 10.1177/1526602815587261
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Blood Flow in Branched and Fenestrated Stent-Grafts for Endovascular Repair of Abdominal Aortic Aneurysms

Abstract: Reliability of antegrade and retrograde stent-grafts, collectively known as branched stent-3 grafts (BSG), has not been appropriately analysed. This computational study assesses the 4 haemodynamic outcomes of BSG for different anatomical variations. 5Methods 6 Ideal models of BSG and fenestrated stent-grafts (FSG) were constructed with different 7 visceral take-off angles (TOA) and lateral aortic neck angle. TOA was defined as the angle 8 between the centrelines of the main stent-graft and side branch, with 90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 20 publications
3
37
0
Order By: Relevance
“…14 The model design played a pivotal role in the computational simulation. Two previous studies analysed the haemodynamic variation resulting from fenestration misalignment, 15,16 with RSGs rising vertically from the fenestration then facing towards different directions. In the present study custom-made fenestrated models were designed with RSGs protruding into the stent graft body, which may constitute a more accurate description in terms of conforming to clinical reality.…”
Section: Discussionmentioning
confidence: 99%
“…14 The model design played a pivotal role in the computational simulation. Two previous studies analysed the haemodynamic variation resulting from fenestration misalignment, 15,16 with RSGs rising vertically from the fenestration then facing towards different directions. In the present study custom-made fenestrated models were designed with RSGs protruding into the stent graft body, which may constitute a more accurate description in terms of conforming to clinical reality.…”
Section: Discussionmentioning
confidence: 99%
“…Based on monitoring the Courant number in pulsatile flow simulations, a uniform 0.02 s time-step was adopted. As suggested by Kandail et al [7], simulations for all geometries were performed for four cardiac cycles to achieve periodic results.…”
Section: B Boundary Conditionsmentioning
confidence: 99%
“…As a first step towards understanding post-surgical complications of FEVAR, including AKI and renal artery thrombosis, this study aims to use computational fluid dynamics (CFD) to determine how fenestration misalignment impacts renal artery hemodynamics. Two factors, renal artery flow rate and renal artery time-averaged wall shear stress (TAWSS) were adopted as hemodynamics indices [6][7][8][9][10] to indicate the risks of AKI and renal thrombosis.…”
Section: Introductionmentioning
confidence: 99%
“…Intuitively, antegrade seems like the better option if one is concerned with increasing flow through the conduit; however, a previous report that used CFD to investigate antegrade and retrograde configurations 6 showed this is not the case, as a retrograde configuration provided an equal flow rate, especially in lengths applicable to branched AAA stent-grafts. Kandail et al 5 have built on this foundation, however, in their geometries, demonstrating that retrograde BSGs underperform in terms of flow to the renal arteries compared to antegrade BSGs and FSGs in all ToAs investigated. The retrograde BSGs also supplied less blood to the kidneys when the neck angle was increased to 60°.…”
mentioning
confidence: 99%
“…Also, a recent investigation into the number of cardiac cycles required to achieve robust convergence of CFD simulations has identified that more than three cycles may be needed. 8 In Kandail et al, 5 as is common in many previous reports, [9][10][11][12] data were deemed repeatable from the third or fourth cycle onward.…”
mentioning
confidence: 99%